Multi-Criteria Decision-Making for Cement Plant Location Selection Using SMART Method: A Case Study of PT. RKB - Toman Nico Felani Sihombing; Utomo Sarjono Putro (Research Synergy Foundation, 2024)
The strategic selection of a cement plant location is crucial for optimizing operational efficiency, sustainability, and market positioning. This study examines the optimal location for PT. RKB's new cement plant in West Java, Indonesia, uses the quantitative Simple Multi-Attribute Rating Technique (SMART) within a Multi-Criteria Decision-Analysis (MCDA) framework. The SMART method transforms various criteria into measurable insights, ensuring a systematic evaluation of alternative sites. Key criteria included economic viability, technical feasibility, environmental impact, and socio-economic considerations. A comprehensive analysis of three potential sites revealed Location C as the most suitable, offering the best balance of economic benefits, technical advantages, manageable environmental impacts, and strong community support. Sensitivity analysis confirmed the robustness of this decision under various scenarios. This study provides a data-driven methodology for strategic site selection in the cement industry, contributing to PT. RKB's sustainable growth and competitive positioning. Theoretically, this research advances the application of MCDA in industrial site selection, while practically, it offers a replicable model for decision-makers in similar industries.